The influence of security perception and consumer trust on repurchase intention on e-commerce platforms - Lisdayanti, Annisa; Hapsari, Ayuningtyas Yuli (Technium Business and Management, 2024)
This study aims to elucidate the impact of security perceptions and consumer trust on repurchase intention on the Shopee Indonesia e-commerce platform. The accelerated growth of e-commerce in Indonesia has yielded considerable advantages for consumers, yet it has also prompted apprehensions regarding the security of personal data. The objective of this study is to examine the influence of security perception and consumer trust on repurchase intention and to provide recommendations for Shopee to enhance both factors. The research method employed is a descriptive and verificative analysis with an iteration sampling technique. A minimum of 116 respondents were included in the study, selected through purposive sampling. The findings indicate that security perception exerts a significant influence on repurchase intention, accounting for 16.89% of the total effect. Conversely, consumer trust demonstrates a more pronounced impact, contributing 48.58% to the overall effect. The combined influence of these two variables on consumer repurchase intention on Shopee Indonesia is 50.4%. This study concludes that security perception and consumer trust play an important role in driving repurchase intention on e-commerce platforms. Therefore, Shopee Indonesia must continuously improve security aspects and build consumer trust to maintain and increase repurchase intention.